Peran Komunikasi Pembangunan dalam Mewujudkan Smart Village di Aceh - Taufik (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
The development of Information and Communication Technology (ICT) has been pivotal in realizing the concept of Smart Village in Aceh. Smart Village is a development strategy aimed at improving the quality of life in rural communities through the integration of technology to accelerate economic development, enhance public service efficiency, and promote environmental sustainability. Development communication plays a central role in this process, acting as a link between government, communities, and the private sector in implementing innovative solutions. Through collaborative approaches involving government, academia, and industry, and utilizing participatory methods that engage local communities, development communication can raise awareness, enhance skills, and facilitate technology adoption at the village level. However, efforts to achieve Smart Village in Aceh are not without challenges. These challenges include uneven ICT infrastructure, community readiness to adopt new technologies, and cultural differences that can affect program sustainability. Strengthening collaboration among stakeholders and implementing inclusive and sustainable communication strategies, the role of development communication will continue to be crucial in achieving sustainable and equitable Smart Village goals in Aceh.